Pendidikan Anak Usia Dini Dalam Perspektif Filsafat Pendidikan Islam - Hindun Smith; Radjiman Ismail; Natsir Machmud (Jurnal Ilmiah Wahana Pendidikan, 2023)
Philosophy as a process of logical, systematic, radical and universal thinking is one of the foundations in the world of education. For Early Childhood Children who are the forerunners of the nation's next generation, Education is a very urgent right and necessity of life that is fulfilled optimally. Discussions related to Early Childhood Education are examined from the point of view of well-known intelligent philosophers who are discussed in more depth in this paper using a Literature Study approach and are described qualitatively. The three figures have almost the same perspective, placing Religious and Moral Education as the initial foundation for children in learning and the family as the first and foremost educator who is fully responsible for children's needs for Education.